Workshop Hands On Preservation Microfilming, Lisbon, February 2006 - van Dormolen, Hans; Cabral, Maria Luísa (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
On February 23 and 24 of 2006, a Workshop on Preservation Microfilming was held at the National Library of Portugal in Lisbon. The workshop was set up as a joint initiative of the Biblioteca Nacional (Lisbon) and the Koninklijke Bibliotheek (The Hague), and carried out under the umbrella of LIBER Preservation Division and with the sponsorship of Scan System, a Portuguese microfilm/scan company, the only commercial party involved. The Workshop aimed to raise awareness about technical issues that can affect the quality of microfilms. Since the meeting was set up as a workshop, the number of attendants was limited to 15 in order to guarantee a hands on approach. The participants consisted of people working for the national libraries and several archives of Portugal and Spain. Scan System, Hans van Dormolen, Quality Manager Microfilming of Metamorfoze, the national preservation program of the Netherlands, led the Workshop. For some time, the idea of organizing a hands on workshop was discussed at divisional meetings. The annual conference never seemed the appropriate place for such a workshop. The Liber 34th Annual Conference 2005 in Groningen, the Netherlands (July 2005) proved to be a turning point; at that occasion, Hans van Dormolen presented a paper raising very serious issues about the quality of preservation microfilms that are being produced. The technical issues he tackled are a matter of concern to every unit involved in microfilming. His paper raised enough interest to put the workshop on the move. Since the LIBER Preservation Division has been trying to involve colleagues from Portugal and Spain in LIBER activities for some time, the decision was made to grasp the opportunity and to organize the workshop in the South of Europe.